PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA VISUAL PEMBELAJARAN WUJUD BENDA DI MIS IKHWANUL MUSLIMIN - Anggriani, Dewi; Wulandari, Karti; Sihombing, Rindawati; Tanjung, Yuli (Cahaya Ilmu Bangsa Institute, 2025)
This research is a Classroom Action Research or commonly called PTK, which aims to improve the learning outcomes of students. This PTK was carried out in class III MIS Ikhwanul Muslimin, Sirandorung District by applying visual media to the learning material of the form of objects in class III MIS in November 2023. The subjects of this classroom action research were class III students with a total of 28 students. This study consisted of two learning cycles, each cycle consisting of two meetings. In addition, several instruments were used to control learning activities, namely observation sheets, interview guidelines, and test questions. The results of the study showed that the learning outcomes of class III MIS Ikhwanul Muslimin students had increased by using the role of visual image media. The increase in the completeness of learning outcomes from Cycle I was 43%. Furthermore, in Cycle II there was an increase of 100%. This shows an increase of 57%. The increase in student learning outcomes was due to the application of visual image media that provided meaningful learning and provided experience and fostered enthusiasm for students so that they were able to optimize student learning achievements. In addition to improving learning outcomes, in the teaching and learning process students show activeness, students appear happier and more enthusiastic. Keywords: Classroom Action Research, Visual Media Images Abstrak Penelitian ini merupakan Penelitian Tindakan Kelas atau biasa disebut PTK, yang bertujuan untuk meningkatkan kemampuan hasil belajar peserta didik. PTK ini dilaksanakan di kelas III MIS Ikhwanul Muslimin Kecamatan Sirandorung dengan menerapkan media visual pada materi pembelajaran wujud benda di kelas III MIS pada bulan November 2023. Subjek penelitian tindakan kelas ini adalah peserta didik kelas III dengan jumlah 28 siswa. Penelitian ini terdiri dari dua siklus pembelajaran, setiap siklus terdiri dari dua kali pertemuan. Selain itu juga untuk mengontrol kegiatan pembelajaran digunakan beberapa instrumen, yaitu lembar observasi, pedoman wawancara, dan soal tes. Hasil penelitian menunjukkan bahwa hasil belajar siswa kelas III MIS Ikhwnaul Muslimin sudah mengalami peningkatan dengan menggunakan peranan media visual gambar. Peningkatan ketuntasan hasil belajar dari Siklus I sebesar 43%. Selanjutnya pada Siklus II terjadi peningkatan 100%. Hal ini menunjukkan terjadi peningkatan sebesar 57%. Peningkatan hasil belajar peserta didik disebabkan oleh adanya penerapan media visual gambar yang memberikan pembelajaran bermakna dan memberikan pengalaman serta menumbuhkan rasa semangat bagi siswa sehingga mampu mengoptimalkan pencapaian belajar siswa. Selain hasil belajar yang meningkat, pada proses belajar mengajar siswa menunjukkan keaktifan, siswa tampak lebih senang dan antusias. Kata Kunci: Penelitian Tindakan Kelas, Media Visual Gambar